Frequency Mapping of Square Head Expander for Vibration Testing - Mikhael Gilang Pribadi Putra Pratama; Muksin Muksin; Yusuf Giri Wijaya; Nur M. Ula; Agus Harno Nurdin Syah (National Institute of Aeronautics and Space - LAPAN, 2022)
Head expander is a component of an electro-dynamic shaker used for vibration tests in the vertical direction for large-size specimens. This study aims to determine the natural frequency distribution of the head expander across a certain number of predetermined points. This distribution map needs to be known to determine the better placement of future specimens on the head expander. In this study, the determination of natural frequency distribution is done through harmonic analysis (simulation) and experiment to form a contrast between the head expander's ideal condition and the actual condition. The frequency range in the middle of the Head Expander has almost the same value for both data types at 1550-1650 Hz. These results recommend that the best sample placement is in the middle of the Head Expander. The difference between the experimental and simulation low points has a not too far difference, which is 62.5 Hz. In contrast, at the highest value, the two have a quite far difference, which is 180.27 Hz. this difference can be caused by the improper installation of sensors on the Head Expander at certain points.